Efeito da perda de habitat natural sobre a ictiofauna de áreas rasas em um estuário tropical. - Reis-Filho, José Amorim (2013)
Public awareness regarding environmental issues has increased in recent decades. The increasing number of impact assessment studies, management and conservation plans, as well as ecological monitoring studies, demand new and more efficient techniques. We collected fishes and environmental variables in three zones (upper, middle and lower) of a tropical estuary during ebb tide. The aim was to test for differences in fish assemblages along a gradient from freshwater to marine waters and to detect effects of habitat loss in the marginal areas of the estuary. Analyses in the sediment (granulometry, organic matter, dissolved oxygen) and water (dissolved oxygen, temperature, salinity and pH) in samples with different levels of habitat loss. We identified three categories of habitats and correlated with parameters of fish assemblages (density, biomass, richness, length and trophic guilds). A total of 77 species were recorded, forming two distinct fish assemblages, with family Eleotridae dominating in the upper, Gerreidae, Gobiidae and Tetraodontidae in the middle and lower estuary. Changes in the structure of fish assemblages as a reduction in density, biomass and richness were associated with habitat loss of natural features (muddy sediment replaced by sandy sediment, organic matter reduction). Dormitatus maculatus in upper estuary and Atherinella brasiliensis in the middle and lower estuary were the species that showed preference for the impacted areas and can serve as indicators of habitat loss due to silting marginal.